ROTATIONAL CONICS

Given that:

Therefore, x = r cosθ = r cos(θ-α)

and y = r sinθ and = r sin(θ-α)

Using the General Addition Formulas1, 2, we have: = x cosα + y sinα = y cosα – x sinα and x= y= cosα sinα + sinα cosα Rotation Transformation Equations

To get the angle of rotation of the plane in which the xy coefficient disappears, we equate the coefficients of the transformed general equation to zero. We get3: cot2α = A-C B

Almira xD

To know the graph of the tranformed equation beforehand, we make use of the discriminant. Take note that4:
2

- 4Ā = B2 - 4AC

And so, If Ā > 0, then it is an ellipse, with B2 – 4AC < 0 Ā = 0, either Ā=0 or =0, then it is a parabola, with B2 – 4AC = 0 Ā < 0, then it is a hyperbola, with B2 – 4AC > 0

PROVING
1

= r cos(θ-α) = r (cosθcosα + sinθsinα) = (r cosθ)(cosα) + (sinθ)(r sinα) = x cosα + y sinα

= r sin(θ-α) = r (sinθcosα - cosθsinα) = (r sinθ)(cosα) – (r cosθ)(sinα) = y cosα – x sinα

2

x = r cosθ = r ( (cosα)(cos(θ-α)) - (sinα)(sin(θ-α)) ) = (r (cos(θ-α)))(cosα) – (r (sin(θ-α)))(sinα) = cosα sinα

y = r sinθ = r ( (sinα)(cos(θ-α)) + (cosα)(sin(θ-α)) ) = (r (cos(θ-α)))(sinα) + (r (sin(θ-α)))(cosα) = sinα + cosα

3

Ax2 = Acos2α

2

– 2Asinαcosα
2

+ Asin2α B(cos2α-sin2α) + Ccos2α
2

2

0 = B(cos2α - sin2α) + (C-A)(2sinαcosα) = Bcos2α + (C-A)(sin2α) Bcos2α = (A-C)(sin2α) cos2α/sin2α = (A-C)/B cot2α = (A-C)/B

Bxy=Bsinαcosα( Cy2 = Csin2α
2

-

2

)+

+ 2Csinαcosα

Almira xD

4

From the transformation of general equation (above), Ā = Acos2α + Bsinαcosα + Csin2 α = B(cos2α - sin2α) + (C-A)(2sinαcosα) = Asin2α - Bsinαcosα + Ccos2α

Then, B2-4AC

2

- 4Ā

(B(cos2α - sin2α) + (C-A)(2sinαcosα))2 – 4(Acos2α + Bsinαcosα + Csin2α) (Asin2α - Bsinαcosα + Ccos2α) B2cos4α -2B2cos2αsin2α + B2sin4α +4(BC-AB)(sinαcos3α) +4(AB-BC)(sin3αcosα) + 4C2sin2αcos2α -8ACsin2αcos2α +4A2sin2αcos2α -4A2sin2 αcos2α +24B2sin2αcos2α -4C2sin2αcos2α -4AC(sin4α+cos4α) -4(BC-AB)(sinαcos3α) -4(AB-BC)(sin3αcosα) B2cos4α + B2sin4α -8ACsin2αcos2α +2B2sin2 αcos2α -4AC(sin4 α+cos4α) B2(cos4α+sin4α+2sin2αcos2α) – 4AC(2sin2αcos2α+ cos4α+sin4α) (B2-4AC)(cos2α+sin2α)2 (B2-4AC)(1)2 ≡ B2-4AC

Almira xD

Sign up to vote on this title
UsefulNot useful